Etika Komunikasi dan Public Speaking dalam Program Berita Televisi Liputan 6 SCTV - Mutiara, Jeaniffer; Herawati, Dewi Maria (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2023)
Abstract News presenters have a responsibility to carry the news or message their communication technique skills. However, circulating video recordings containing the unprofessional behavior of the news presenter. There was a sound leak from the coverage team at the time of broadcasting and allegedly offended a guest who was present at the funeral. This study aims to determine the ability of public speaking and communication ethics standards of news presenters in presenting the news program Liputan 6 SCTV. The research method used is descriptive qualitative research method. The results of this study indicate the existence of special public speaking skills that a presenter must have. This shows that speaking skills are able to shape someone to be alert in dealing with any situation and quickly deal with problems that occur when doing assignments directly in the studio or in the field. As well as the application of communication ethics standards in general and based on the vision and mission of the communication ethics standards owned by Liputan 6 SCTV. So that through communication ethics one can build relationships with the community through the applicable ethical standards of communication and be responsible for the applicable code of ethics.Keywords: Communication Ethic; Public Speaking; Descriptive Analysis Abstraksi Presenter disebut juga sebagai Newsanchor yang memiliki tanggungjawab dalam membawakan berita atau pesan seputar kehidupan masyarakat Indonesia dan dunia dengan kemampuan teknik komunikasi yang dimiliki. Berdasarkan fenomena yang pernah terjadi dan dialami oleh Presenter yang sedang membawakan berita di televisi dimana rekaman video tersebut viral dengan perilaku Presenter yang tidak professional. Penelitian ini bertujuan untuk mengetahui kemampuan public speaking dan standar etika komunikasi seorang Presenter dalam membawakan sebuah program berita Liputan 6 SCTV. Metode penelitian yang digunakan adalah metode penelitian kualitatif deskriptif dengan data primernya diperoleh dari wawancara dan observasi, sedangkan data sekundernya diperoleh dari dokumentasi. Teori yang digunakan adalah teori Etika Komunikasi dan teori Public Speaking. Hasil penelitian ini menunjukkan adanya kemampuan public speaking yang harus dimiliki seorang Presenter dan menerapkan standar etika komunikasi secara umum bahkan berdasarkan visi, misi dari standar etika komunikasi yang dimiliki Liputan 6 SCTV. Presenter Liputan6 juga melakukan praktik di lapangan dan studio dengan memanfaatkan waktu dan properti yang tersedia untuk digunakan sebagai latihan untuk menjadi Presenter Liputan6 yang kompeten.Kata Kunci: Etika Komunikasi, Presenter, Public Speaking, Analisis deskriptif